FORMULATION AND ANTIOXIDANT ACTIVITY OF SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM) (SNEDDS) FALOAK BARK - Yorida Febry Maakh (JURNAL KATALISATOR, 2021)
Flavanoids and 3-hydroxy-octadecanoic acid in Faloak bark (Sterculiaquadrifida R. Br) have low water solubility then it is formulated in the form of SNEDDS to increase the solubility. This study aimed to formulate and measure the antioxidant activity of SNEDDS ethanolic extract of faloak bark. The optimum SNEDDS formula is characterized by percent transmittance, emulsification time in artificial gastric fluid (AGF), stability in artificial gastric fluid (AGF), and artificial intestinal fluid (AIF). The ethanol extract of Faloak bark and the optimum formula of Faloak bark was tested for their reducing activity against DPPH. The results of the SNEDDS formula composition of the optimum Faloak bark extract consisted of VCO, Tween 80, and PEG 400 in a ratio of 1: 6.65: 0.35 (ml) which could carry 7.14 mg per mL of Faloak bark extract. The optimum SNEDDS formula produces homogeneous and clear nano emulsions with transmittance values of 88.81 ± 0.02%, emulsification time in AGF of 6.53 ± 0.02 seconds, and stable in AGF and unstable in AIF media. IC50 value of ethanol extract of Faloak bark and optimal formula each has antioxidant activity with a very strong intensity (38,511 ppm) and strong (70,182 ppm).